Features of theoretical training in combative sports - Pityn, M.; Briskin, Y.; Zadorozhna, O. (Journal of Physical Education and Sport, 2013)
The article deals with the theoretical training as a major driver of the effectiveness of the training process of athletes at different stages of long-term training in combative sports. Purpose: The Purpose is determination of problem aspects of theoretical training in combative sports (fencing and taekwondo). Results: Theoretical training is realized from 4 hours to 30 hours of total training load at various stages of long-term development in fencing (from 1,2 % to 1,8 %). In taekwondo theoretical training is realized from 6 hours to 69 hours of total training load at various stages of long-term development (from 1,9 % to 3,9 %). Negative aspects of theoretical training in a group of combat sports are the lack of specificity and differentiation of means and methods of theoretical training at different stages of development, the lack of information structuring in long-term training, neglecting of control in the theoretical training of athletes.